The Cultural Value of the Kayori Ceremony of the Pendau Tribe as Seen from the Civic Culture of the Siweli Village Community, Balaesang District - Cinta Arfa; Shofia Nurun Alunur; Hasdin; Nasran; Sunarto Amus; Sukmawati (Institut Agama Islam Negeri Ponorogo, 2026)
Previous studies on the Kayori Ceremony of the Pendau Tribe have tended to focus on linguistic and literary analysis, leaving a research gap in the perspective of Civic Education. This study aims to fill this gap by exploring the cultural values within the Kayori Ceremony and its unique contribution to the formation of civic culture in Siweli Village. Using a descriptive qualitative method with an ethnographic approach, data were collected through participant observation, in-depth interviews with 8 informants (traditional leaders, village officials, and youth), and documentation. The novelty of this research reveals that the Kayori Ceremony is not merely a mystical ritual but also functions as a